2019
DOI: 10.1002/ptr.6359
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits growth and metastasis of human gastric cancer cell MKN45 by down‐regulating microRNA‐21

Abstract: Celastrol could inhibit cancer cell growth in vitro. However, effect(s) of celastrol on gastric cancer is not well studied. Therefore, we investigated the effects of celastrol on human gastric cancer cell line MKN45 and the underlying mechanisms. We found that celastrol inhibited cell proliferation, migration, and invasion and induced cell apoptosis and G2/M cell cycle arrest (p < .05, p < .01, or p < .001). Under celastrol treatment, overexpression of microRNA‐21 (miR‐21) increased cell viability, migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Previous studies confer that Cel inhibits cancer growth, inflammation and cardiac fibrosis. 9,40,41 In the present study, we found that a new target (i.e. miR-345-5p) of Cel was activated in HG-stimulated cardiomyocyte, whereas Cel administration could neutralize HG-induced up-regulation of miR-345-5p expression.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies confer that Cel inhibits cancer growth, inflammation and cardiac fibrosis. 9,40,41 In the present study, we found that a new target (i.e. miR-345-5p) of Cel was activated in HG-stimulated cardiomyocyte, whereas Cel administration could neutralize HG-induced up-regulation of miR-345-5p expression.…”
Section: Discussionsupporting
confidence: 51%
“…Celastrol possesses multiple pharmacological effects and showed potent anti-inflammatory effect against many disease models, [10][11][12][13] and however, few reports can be seen regarding the anti-inflammatory potential of celastrol in liver fibrosis. SIR2 is a family of histone deacetylases and is widely distributed in cells with multiple functions.…”
Section: The Active Ingredients Extracted From Traditional Chinesementioning
confidence: 99%
“…The active ingredients extracted from Traditional Chinese Medicine have become important choices for the treatment of several chronic diseases, including liver fibrosis . Celastrol is a pentacyclic triterpenoid compound (the chemical structure of celastrol is shown in Figure ), which is isolated from a common clinical used Traditional Chinese Medicine named Tripterygium wilfordii Hook F. Celastrol possesses multiple pharmacological effects and showed potent anti‐inflammatory effect against many disease models, and however, few reports can be seen regarding the anti‐inflammatory potential of celastrol in liver fibrosis. SIR2 is a family of histone deacetylases and is widely distributed in cells with multiple functions .…”
Section: Introductionmentioning
confidence: 99%
“…Some miRNAs, such as miR-4670-5p, miR-940, miR-493, miR-30e, and miR-7, have been shown to have antitumor effects both in vitro and in vivo, [99][100][101][102] and other miRNAs, such as miR-494, miR-124, miR-34a, miR-21, and miR-9, have been investigated in more than one study. [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114]…”
Section: Microrna-based Other Therapiesmentioning
confidence: 99%